The Role Of The Prosecutor in Optimizing The Implementation of Criminal Sentences in Additional to the Payment of Supervisory Money by Convicted Corruption Criminal Acts (The Dilemmatic of Supervisory Money Recorded as State Receivables) - Sulis Setyowati; Saan Saan; Guntarto Widodo (Lembaga Teewan Journal Solutions, 2026)
This study examines the role of the executing prosecutor in optimizing the enforcement of additional criminal sanctions in the form of compensation payments imposed on convicted corruption offenders. The execution process involves asset tracing, asset seizure, public auction of confiscated property, asset impoverishment, and the imposition of substitute imprisonment when compensation cannot be recovered. A legal issue arises when a convicted person has completed the substitute imprisonment sentence but still has an unpaid compensation obligation, which is subsequently recorded as a state receivable. As long as the receivable remains outstanding, it continues to be reported in the execution records of the Prosecutor’s Office of the Republic of Indonesia and creates administrative burdens. This research employs a normative juridical method using statutory, case, and conceptual approaches. Data were collected through documentary research and analyzed using qualitative descriptive analysis. The findings indicate that the execution of compensation payments is based on the Supreme Court Regulation of the Republic of Indonesia Number 5 of 2014 and the Attorney General’s regulations governing corruption law enforcement. The amount of compensation corresponds to the financial loss suffered by the state, calculated using either the net loss or total loss method. Therefore, this study recommends establishing a legal mechanism for writing off uncollectible state receivables to ensure legal certainty, reduce administrative burdens, and improve the effectiveness of executing corruption judgments.